REGULATION OF THE HORIZONTAL RELATIONS IN THE CONSTITUTION OF THE REPUBLIC OF POLAND - Florczak-Wątor, Monika (Teisė, 2015)
Regulation of horizontal relations (that is, relations between individuals) at the constitutional level is a phenomenon that is commonly found at the present time in democratic countries. To some extent this is a departure from the traditional model of the constitution as the legal act that regulates relations between an individual and the state (vertical relations), although of course this latter issue is still the main subject of constitutional regulation. Next to vertical relations, as if in parallel, contemporary constitutions increasingly regulate completely different categories of legal relations, to which the state is not a party, such as the relations between employers and employees, parents and children, and entrepreneurs and consumers. This kind of horizontal relationship is also the subject of regulation under the Constitution of the Republic of Poland adopted by the National Assembly on 2nd April 1997. I would therefore like to consider the type of horizontal relations that are covered by constitutional regulation, the extent to which regulation affects these relations, and the significance of regulation. However, the text of the Constitution of the Republic of Poland will only be the starting point for the formulation of more general conclusions that – I strongly believe – are also suitable for many other European constitutional regulations. [...]